Role of the thymus in natural tolerance to an autologous protein antigen (The Rockefeller University Press, 1989)
C5-deficient mice grafted with thymus from C5-sufficient donors and immunized with C5 failed to make humoral antibody to C5, suggesting that the transfer of thymus had induced tolerance. Irradiated C5- deficient hosts repopulated with lymphoid cells from thymectomized C5- deficient mice grafted with C5-sufficient thymus also failed to respond to immunization with C5, thus showing that the state of tolerance can be adoptively transferred. These results demonstrate that natural tolerance to self-protein antigen is "learned" in the thymus.